İletken polimer tabanlı hibrit güneş pili üretimi ve karakterizasyonu - Örnek, Osman (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2012)
Dünyadaki fosil bazlı enerji kaynaklarının azalması nedeniyle yeni alternatif enerji kaynakları araştırılmaktadır. Bunlardan en temiz ve yenilenebilir enerji kaynağı güneştir. Ülkemiz güneş enerjisi yönünden oldukça avantajlı bir konuma sahiptir. Bugün, harcanan enerjinin oldukça az bir bölümü güneş enerjisinden karşılanabilmektedir. Bunun nedeni güneş pillerinin verimlerinin çok düşük ve üretim maliyetlerinin çok fazla olmasıdır. Bu yüzden, hem güneş pilleri yapmak için ucuz yöntem bulunması hem de mevcut yöntemlerle üretilen güneş pillerinin verimlerini artırıcı çalışmalar yapılması gerekmektedir. İnorganik bazlı güneş pillerinde orta seviyeye yakın verime ulaşılmıştır. Fakat bu güneş pillerinin üretim maliyetlerinin fazla oluşu ve işlenebilirliğinin zor olması, araştırmaları organik güneş pillerine yöneltmiştir.Organik molekül içeren malzemelerle yapılan güneş pillerine organik güneş pili denir. Bu malzemeler istendiğinde bir kaç nanometre kalınlığında ve düşük sıcaklıkta bile kaplanabilmekte ve bant aralıkları ayarlanabilmektedir. Organik güneş pillerinin avantajı; esneklikleri, estetik görüntüleri, hafiflikleri ve ucuz olmalarıdır. İletken polimer tabanlı güneş pili üretiminde, polimer çözeltiler kullanılması güneş pili maliyetini düşürmektedir. Organik pillerin pratikte kullanılabilir hale gelmesi için verimliliğinin artırılması, uzun dönem kararlılığının ve çevre etkenlerine tepkisinin araştırılması gerekmektedir.Bu kapsamda doktora çalışmamda, organik-hibrit güneş pilleri ürettim ve karekterizasyonunu yaptım. Kullandığımız TiO2'in elektron transfer özelliğini geliştirebilmek için TiO2 kristal örgü içine çeşitli geçiş metalleri (Mn, Ni, Co ve Cu) katkılamayı denedim ve katkılamanın pil performansı üzerinde etkisini inceledim. Öncelikle TiO2 kristal örgü içine çeşitli oranlarda Mn katkıladım ve bu TiO2 ve katkılı TiO2'lerle hazırlanan güneş pillerinin performans analizini yaptım. Mn katkılı TiO2 Kristalinin SEM görüntüleri, katkılı ve katkısız TiO2 ince filmlerin XRD grafikleri ve Akım-Voltaj eğrileri incelenmiştir. Mn ve Co katkılı TiO2 ince filmli organik güneş pillerinin verimlerinin, katkısız TiO2 ince filmli olanlara göre önemli ölçüde arttığı tespit edilmiştir. Diğer geçiş elementlerinin (Ni ve Cu) değişik oranlarında yaptığımız katkı çalışmalarında kayda değer sonuçlara ulaşılamamıştır.

New alternative energy sources are investigated because of the decline of fossil-based energy resources in the world. The Sun, which is the cleanest and a renewable energy source, is one of these. Our country has quite rich advantageous position in terms of using solar energy. At present, it is very small part of the whole energy consumption that is supplied by solar batteries. This is because the solar batteries are at low productivity and their production costs are considerably high. Therefore, it is a necessity to find a cheaper method in solar battery production, also to make researches for increasing the productivity of the solar batteries that are produced by existing methods. Close to the middle level of efficiency has been reached in inorganic-based solar batteries. But mainly because the cost of production and functionality are difficult, research has been done in organic solar batteries.Solar batteries, which are produced with materials containing organic molecules, are named as organic solar batteries. These materials are venerable on demand at a few nanometers of thickness and even at low temperatures, and bandwidth can also be adjusted. The advantages of organic solar batteries are their flexibility, esthetical view, weightlessness and inexpensiveness. Using polymer solutions in producing conductor polymer based solar battery reduces the solar battery production costs. In order to make solar batteries practicable, it is necessary to increase their productivity and to investigate their long-term stability and their reactions against the environmental factors.In my doctoral study, I have produced organic-hybrid solar battery, and made characterization of it. I have tried to dope various transition metals (Mn, Ni, Co and Cu) into the TiO2 crystal lattice in order to improve the electron transfer characteristic of TiO2 that we use in organic-hybrid solar battery design and we have analyzed the effect of the doping on the battery performance. Primarily, we have doped Mn at various rates into the TiO2 crystal lattice and we have carried out the performance analysis of the solar batteries that are produced with TiO2 and with TiO2 containing additive. SEM images of TiO2 Crystal with Mn additive, XRD graphics of additive and non-additive TiO2 thin films and Current-Potential curves are investigated. Mn and Co were doped into the TiO2 crystal lattice at various rates and it was observed that the productivity of the batteries produced were altered. However, there was no significant result when we carried out the doping study of the other transition elements (Ni and Cu) at various rates.SUMMARYTOPIC OF THE THESIS: PRODUCTION and CHARACTERIZATION OF CONDUCTOR POLYMER BASED HYBRID SOLAR BATTERYAUTHOR OF THE THESIS: OSMAN ÖRNEKNew alternative energy sources are investigated because of the decline of fossil-based energy resources in the world. The Sun, which is the cleanest and a renewable energy source, is one of these. Our country has quite rich advantageous position in terms of using solar energy. At present, it is very small part of the whole energy consumption that is supplied by solar batteries. This is because the solar batteries are at low productivity and their production costs are considerably high. Therefore, it is a necessity to find a cheaper method in solar battery production, also to make researches for increasing the productivity of the solar batteries that are produced by existing methods. Close to the middle level of efficiency has been reached in inorganic-based solar batteries. But mainly because the cost of production and functionality are difficult, research has been done in organic solar batteries.Solar batteries, which are produced with materials containing organic molecules, are named as organic solar batteries. These materials are venerable on demand at a few nanometers of thickness and even at low temperatures, and bandwidth can also be adjusted. The advantages of organic solar batteries are their flexibility, esthetical view, weightlessness and inexpensiveness. Using polymer solutions in producing conductor polymer based solar battery reduces the solar battery production costs. In order to make solar batteries practicable, it is necessary to increase their productivity and to investigate their long-term stability and their reactions against the environmental factors.In my doctoral study, I have produced organic-hybrid solar battery, and made characterization of it. I have tried to dope various transition metals (Mn, Ni, Co and Cu) into the TiO2 crystal lattice in order to improve the electron transfer characteristic of TiO2 that we use in organic-hybrid solar battery design and we have analyzed the effect of the doping on the battery performance. Primarily, we have doped Mn at various rates into the TiO2 crystal lattice and we have carried out the performance analysis of the solar batteries that are produced with TiO2 and with TiO2 containing additive. SEM images of TiO2 Crystal with Mn additive, XRD graphics of additive and non-additive TiO2 thin films and Current-Potential curves are investigated. Mn and Co were doped into the TiO2 crystal lattice at various rates and it was observed that the productivity of the batteries produced were altered. However, there was no significant result when we carried out the doping study of the other transition elements (Ni and Cu) at various rates.SUMMARYTOPIC OF THE THESIS: PRODUCTION and CHARACTERIZATION OF CONDUCTOR POLYMER BASED HYBRID SOLAR BATTERYAUTHOR OF THE THESIS: OSMAN ÖRNEKNew alternative energy sources are investigated because of the decline of fossil-based energy resources in the world. The Sun, which is the cleanest and a renewable energy source, is one of these. Our country has quite rich advantageous position in terms of using solar energy. At present, it is very small part of the whole energy consumption that is supplied by solar batteries. This is because the solar batteries are at low productivity and their production costs are considerably high. Therefore, it is a necessity to find a cheaper method in solar battery production, also to make researches for increasing the productivity of the solar batteries that are produced by existing methods. Close to the middle level of efficiency has been reached in inorganic-based solar batteries. But mainly because the cost of production and functionality are difficult, research has been done in organic solar batteries.Solar batteries, which are produced with materials containing organic molecules, are named as organic solar batteries. These materials are venerable on demand at a few nanometers of thickness and even at low temperatures, and bandwidth can also be adjusted. The advantages of organic solar batteries are their flexibility, esthetical view, weightlessness and inexpensiveness. Using polymer solutions in producing conductor polymer based solar battery reduces the solar battery production costs. In order to make solar batteries practicable, it is necessary to increase their productivity and to investigate their long-term stability and their reactions against the environmental factors.In my doctoral study, I have produced organic-hybrid solar battery, and made characterization of it. I have tried to dope various transition metals (Mn, Ni, Co and Cu) into the TiO2 crystal lattice in order to improve the electron transfer characteristic of TiO2 that we use in organic-hybrid solar battery design and we have analyzed the effect of the doping on the battery performance. Primarily, we have doped Mn at various rates into the TiO2 crystal lattice and we have carried out the performance analysis of the solar batteries that are produced with TiO2 and with TiO2 containing additive. SEM images of TiO2 Crystal with Mn additive, XRD graphics of additive and non-additive TiO2 thin films and Current-Potential curves are investigated. Mn and Co were doped into the TiO2 crystal lattice at various rates and it was observed that the productivity of the batteries produced were altered. However, there was no significant result when we carried out the doping study of the other transition elements (Ni and Cu) at various rates.SUMMARYTOPIC OF THE THESIS: PRODUCTION and CHARACTERIZATION OF CONDUCTOR POLYMER BASED HYBRID SOLAR BATTERYAUTHOR OF THE THESIS: OSMAN ÖRNEKNew alternative energy sources are investigated because of the decline of fossil-based energy resources in the world. The Sun, which is the cleanest and a renewable energy source, is one of these. Our country has quite rich advantageous position in terms of using solar energy. At present, it is very small part of the whole energy consumption that is supplied by solar batteries. This is because the solar batteries are at low productivity and their production costs are considerably high. Therefore, it is a necessity to find a cheaper method in solar battery production, also to make researches for increasing the productivity of the solar batteries that are produced by existing methods. Close to the middle level of efficiency has been reached in inorganic-based solar batteries. But mainly because the cost of production and functionality are difficult, research has been done in organic solar batteries.Solar batteries, which are produced with materials containing organic molecules, are named as organic solar batteries. These materials are venerable on demand at a few nanometers of thickness and even at low temperatures, and bandwidth can also be adjusted. The advantages of organic solar batteries are their flexibility, esthetical view, weightlessness and inexpensiveness. Using polymer solutions in producing conductor polymer based solar battery reduces the solar battery production costs. In order to make solar batteries practicable, it is necessary to increase their productivity and to investigate their long-term stability and their reactions against the environmental factors.In my doctoral study, I have produced organic-hybrid solar battery, and made characterization of it. I have tried to dope various transition metals (Mn, Ni, Co and Cu) into the TiO2 crystal lattice in order to improve the electron transfer characteristic of TiO2 that we use in organic-hybrid solar battery design and we have analyzed the effect of the doping on the battery performance. Primarily, we have doped Mn at various rates into the TiO2 crystal lattice and we have carried out the performance analysis of the solar batteries that are produced with TiO2 and with TiO2 containing additive. SEM images of TiO2 Crystal with Mn additive, XRD graphics of additive and non-additive TiO2 thin films and Current-Potential curves are investigated. Mn and Co were doped into the TiO2 crystal lattice at various rates and it was observed that the productivity of the batteries produced were altered. However, there was no significant result when we carried out the doping study of the other transition elements (Ni and Cu) at various rates.
Production and characterization of conductor polymer based hybrid solar battery
Keywords: Fizik ve Fizik Mühendisliği; Physics and Physics Engineering